A Replicable NeuroMark Template for Whole-Brain SPECT Reveals Data-Driven Perfusion Networks and Their Alterations in Schizophrenia - Amritha Harikumar; Bradley Baker; Daniel Amen; David Keator; Vince D. Calhoun (Neuroinformatics, 2026)
Single photon emission computed tomography (SPECT) is a highly specialized imaging modality that enables measurement of regional cerebral perfusion and, in particular, regional cerebral blood flow (rCBF). Recent technological advances have improved SPECT quantification and reliability, making it increasingly useful for studying rCBF abnormalities and perfusion–network alterations in psychiatric and neurological disorders. To characterize large-scale functional organization in SPECT data, data-driven decomposition methods such as independent component analysis (ICA) have been used to extract covarying perfusion patterns that map onto interpretable brain networks. Blind ICA provides a data-driven approach to estimate these networks without strong prior assumptions. More recently, a hybrid approach that leverages spatial priors to guide a spatially constrained ICA (sc-ICA) have been used to fully automate the ICA analysis while also providing participant-specific network estimates. While this has been reliably demonstrated in fMRI with the NeuroMark template, there is currently no comparable SPECT template. A SPECT template would enable automatic estimation of functional SPECT networks with participant-specific expressions that correspond across participants and studies. The current study introduces a new replicable NeuroMark SPECT template for estimating canonical perfusion covariance patterns (networks). We first identify replicable SPECT networks using blind ICA applied to two large sample SPECT datasets. We then demonstrate the use of the resulting template by applying sc-ICA to an independent schizophrenia dataset. In sum, this work presents and shares the first NeuroMark SPECT template and demonstrating its utility in an independent cohort, providing a scalable and robust framework for network-based analyses.

Probabilistic interpolation of crowdsourced meteorological data for higher-resolution gridded estimates of surface air temperature - Zachary D. Calhoun; Mike Bergin; David Carlson (Urban Climate, 2026)

Inherited alterations of TGF beta signaling components in Appalachian cervical cancers - Thomas J. Knobloch; Juan Peng; Erinn M. Hade; David E. Cohn; Mack T. Ruffin; Michael A. Schiano; Byron C. Calhoun; William C. McBee; Jamie L. Lesnock; Holly H. Gallion; Jondavid Pollock; Bo Lu; et al. (Cancer Causes & Control, 2019)

A resting state fMRI analysis pipeline for pooling inference across diverse cohorts: an ENIGMA rs-fMRI protocol - Bhim M. Adhikari; Neda Jahanshad; Dinesh Shukla; Jessica Turner; Dominik Grotegerd; Udo Dannlowski; Harald Kugel; Jennifer Engelen; Bruno Dietsche; Axel Krug; Tilo Kircher; Els Fieremans; et al. (Brain Imaging and Behavior, 2019)

Spatiospectral Decomposition of Multi-subject EEG: Evaluating Blind Source Separation Algorithms on Real and Realistic Simulated Data - David A. Bridwell; Srinivas Rachakonda; Rogers F. Silva; Godfrey D. Pearlson; Vince D. Calhoun (Brain Topography, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

Colorado Potato Beetle Resistance in Solanum oplocense X Solanum tuberosum Intercross Hybrids and Metabolite Markers for Selection - Helen H. Tai; Kraig Worrall; David De Koeyer; Yvan Pelletier; George C. C. Tai; Larry Calhoun (American Journal of Potato Research, 2015)

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Tadalafil-induced improvement in left ventricular diastolic function in resistant hypertension - Rodrigo C. Santos; Ana Paula C. de Faria; Natália R. Barbaro; Rodrigo Modolo; Silvia E. Ferreira-Melo; José R. Matos-Souza; Otávio R. Coelho; Juan C. Yugar-Toledo; Vanessa Fontana; David Calhoun; Heitor Moreno (European Journal of Clinical Pharmacology, 2014)

TERRESTRIAL HABITAT SELECTION AND STRONG DENSITY‐DEPENDENT MORTALITY IN RECENTLY METAMORPHOSED AMPHIBIANS - David A. Patrick; Elizabeth B. Harper; Malcolm L. Hunter; Aram J. K. Calhoun (Ecology, 2008)
To predict the effects of terrestrial habitat change on amphibian populations, we need to know how amphibians respond to habitat heterogeneity, and whether habitat choice remains consistent throughout the life‐history cycle. We conducted four experiments to evaluate how the spatial distribution of juvenile wood frogs, Rana sylvatica (including both overall abundance and localized density), was influenced by habitat choice and habitat structure, and how this relationship changed with spatial scale and behavioral phase. The four experiments included (1) habitat manipulation on replicated 10‐ha landscapes surrounding breeding pools; (2) short‐term experiments with individual frogs emigrating through a manipulated landscape of 1 m wide hexagonal patches; and habitat manipulations in (3) small (4‐m 2 ); and (4) large (100‐m 2 ) enclosures with multiple individuals to compare behavior both during and following emigration. The spatial distribution of juvenile wood frogs following emigration resulted from differences in the scale at which juvenile amphibians responded to habitat heterogeneity during active vs. settled behavioral phases. During emigration, juvenile wood frogs responded to coarse‐scale variation in habitat (selection between 2.2‐ha forest treatments) but not to fine‐scale variation. After settling, however, animals showed habitat selection at much smaller scales (2–4 m 2 ). This resulted in high densities of animals in small patches of suitable habitat where they experienced rapid mortality. No evidence of density‐dependent habitat selection was seen, with juveniles typically choosing to remain at extremely high densities in high‐quality habitat, rather than occupying low‐quality habitat. These experiments demonstrate how prediction of the terrestrial distribution of juvenile amphibians requires understanding of the complex behavioral responses to habitat heterogeneity. Understanding these patterns is important, given that human alterations to amphibian habitats may generate extremely high densities of animals, resulting in high density‐dependent mortality.

Effect of divalent cations on the structure of the antibiotic daptomycin - Steven W. Ho; David Jung; Jennifer R. Calhoun; James D. Lear; Mark Okon; Walter R. P. Scott; Robert E. W. Hancock; Suzana K. Straus (European Biophysics Journal, 2008)

Linearly Organized Turbulence Structures Observed Over a Suburban Area by Dual-Doppler Lidar - Rob Newsom; Ron Calhoun; David Ligon; Jerry Allwine (Boundary-Layer Meteorology, 2008)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Commercial Speech Recognition Technology in the Military Domain: Results of Two Recent Research Efforts - David T. Williamson; Mark H. Draper; Gloria L. Calhoun; Timothy P. Barry (Genetic Resources and Crop Evolution, 2005)

The Correct Phylogenetic Relationship of KdsA (3-Deoxy-D-manno-octulosonate 8-Phosphate Synthase) with One of Two Independently Evolved Classes of AroA (3-Deoxy-D-arabino-heptulosonate 7-Phosphate Synthase) - Roy A. Jensen; Gary Xie; David H. Calhoun; Carol A. Bonner (Journal of Molecular Evolution, 2002)